Contemplating the Opposition: Does a Personal Touch Matter?. Issue 4 (20th April 2020) - Iordanou, Kalypso; Kuhn, Deanna
ABSTRACT: Is it important to hear positions opposing one's own from others who genuinely believe them? We examine whether the thinking of those who engage in discourse with peers who hold an opposing view benefit by hearing arguments favoring the opposing position expressed by individuals known to hold this position. We report on 131 young adolescents who were given access to identical relevant evidence, and engaged in dialogs on gas vs solar energy, in preparation for a whole class debate. In the (randomly assigned) experimental classroom, electronic dialogs were conducted with a series of peers who held an opposing view; in the control classroom, dialogs were confined to same-side peers. Differences in prevalence and types of functional evidence-based argumentive idea units in individual final essays on the topic favored the experimental group. Also, differences by condition in participants' choice of evidence to access during the preceding dialogs reflected differences in patterns of inquiry. Differences appeared as well in post-intervention essays on a non-discourse topic, suggesting the superior group had made gains in understanding argumentation itself. Extension of the study longitudinally to a second year with a new topic showed continued gains and condition differences, supporting this interpretation, with the experimental group surpassing the control group. Potential generalization to adults' discourse on topics involving higher affect and commitment is considered.